Biomedical applications of functional peptides in nano-systems. (September 2018) - Rong, Lei; Qin, Si-Yong; Zhang, Chi; Cheng, Yin-Jia; Feng, Jun; Wang, Shi-Bo; Zhang, Xian-Zheng
Abstract: During the past decades, functionalized nano-systems were believed in holding the bright future of the nanomaterials in biomedical applications. Due to their excellent biocompatibility, biodegradation capability, and biological activity, functional peptides have been vastly used solitary or employed as functional components in nano-systems for disease treatments. This review focuses on the recent advances on the use of functional peptides as a toolbox to construct various delivery nano-systems for tumor treatments. Arising from the special function contributed to the nano-systems, the functional peptides are mainly divided into three groups, cell-targeting peptides (CTPs), cell-penetrating peptides (CPPs), and environment-sensitive peptides. Within each group, their usage in both organic and inorganic systems is discussed. In particular, strategies used to generate promising therapeutic nano-systems for efficient tumor treatment are also highlighted. Graphical abstract: Image 1 Highlights: This work reviews various functional peptides. Functional peptides have been employed to construct different nano-systems. The biomedical applications of these functional nano-systems are included.